Contraindications to Breastfeeding - Current Issues at the Border Between Myth and Reality - ANA MARIA ALEXANDRA STANESCU; ALEXANDRA TOTAN; DANIELA MIRCESCU; IOANA VERONICA GRAJDEANU; BOGDAN SERBAN; OVIDIU GABRIEL BRATU; CAMELIA CRISTINA DIACONU (Modern Medicine)
Breast milk is recommended as an optimal and exclusive source of early nutrition for all infants from birth to at least 6 months of age. Despite all the benefi ts of breastfeeding, there are situations where breastfeeding is contraindicated. There are differences of opinion regarding the contraindications of breastfeeding, the current research bringing more knowledge in this area. It is important to know the differences of opinion for the correct approach of the breastfeeding patient.